Obesity and CRP, Adiponectin, Leptin, and Lipid Profile in Saudi Arabian Adolescent Females - Sawsan Hassan Mahassni ,; Rajaa Braik Sebaa, (Journal of Basic & Applied Sciences, 2013)
Overweight and obesity are increasing tremendously in female Saudi Arabian adolescents. Overweight and obesity lead to many medical risks and affects the immune system. In this study, the effects of obesity on the immune system of 100 Saudi female adolescent students were investigated. Using a blood sample from each subject, the following immune related parameters were determined: concentrations of C-reactive protein (CRP), adiponectin and leptin hormones, and the complete lipid profile. Finally, to assess the body weight status of the subjects and to categorize them, the weight, height, and the waist and hip circumferences were measured to calculate the body mass index (BMI), waist-to-hip ratio (WHR), and the waist circumference (WC). Results show highly significant increases for the CRP and leptin and a highly significant decrease of adiponectin with increasing body weight measured by the three methods. As for the lipid profile, both triglycerides and LDL increased while HDL decreased as body weight increased. Cholesterol did not change with changing body weight measured by the three methods. The findings indicate that obesity seriously affects the immune systems of the subjects and confirm the finding of other researchers that obesity is an inflammatory disease, which explains some health complications associated with obesity.